2020
DOI: 10.3892/or.2020.7648
|View full text |Cite
|
Sign up to set email alerts
|

Identification of early stage recurrence endometrial cancer biomarkers using bioinformatics tools

Abstract: Endometrial cancer (EC) is the sixth most common cancer in women worldwide. Early diagnosis is critical in recurrent EC management. The present study aimed to identify biomarkers of EC early recurrence using a workflow that combined text and data mining databases (DisGeNET, Gene Expression Omnibus), a prioritization algorithm to select a set of putative candidates (ToppGene), protein-protein interaction network analyses (Search Tool for the Retrieval of Interacting Genes, cytoHubba), association analysis of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…These genes were associated with worse overall survival in endometrial cancer. Validated on tissue samples, TPX2 was shown to be relevant for risk assessment especially in grade 1 and 2 endometrial cancer [ 73 ]. Further bioinformatic research with archival sample validation also proposed, that UBE2C could serve as a marker of worse prognosis [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These genes were associated with worse overall survival in endometrial cancer. Validated on tissue samples, TPX2 was shown to be relevant for risk assessment especially in grade 1 and 2 endometrial cancer [ 73 ]. Further bioinformatic research with archival sample validation also proposed, that UBE2C could serve as a marker of worse prognosis [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 depicts the candidate genes adding to the pool of risk stratification markers. The depiction of different markers in Figure 2 and Figure 3 shows, that there is still much unknown about the interactions of different molecular signaling pathways [ 68 , 73 , 74 , 75 ]. The major pathways involved in endometrial cancer seem to be PI3K/Akt/mTOR, MAPK, WNT, and FBXW7 signaling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades, a lot of data mining analysis of mRNA, microRNA, long non-coding RNA, and DNA methylation have been performed on human cancers, including colon cancer [16][17][18][19]. As the biomarkers identified by the above techniques are of diagnostic and prognostic values in cancers and the revolution of sequencing technologies and bioinformatics tools facilitates the identification of more potential biomarkers related to disease progression [20][21][22][23], the more potential biomarkers identified, the more recognition and options for the diagnosis and treatment of colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing clinical trials rely on this new TCGA classification [13,14], but the gene expression data and results published by TCGA also carry in themselves the opportunity for the development of a procedure that could identify high-risk patients and enable better therapeutic planning. By using gene expression measurements, as primary data, certain research groups were able to estimate the prognosis of the disease [15] or they found promising biomarker candidates that were associated with recurrent early-stage endometrial carcinoma [16]. Others who used only clinical features failed to produce a highly accurate model [17].…”
Section: Introductionmentioning
confidence: 99%